(untitled) (The Research of Medical Science Review, 2025)
Background: Dexmedetomidine is an alpha-2 adrenergic agonist with sedative, anxiolytic, and analgesic properties. This study aimed to assess the inhibitory effects of preoperative administration of 0.5 μg/kg dexmedetomidine on hemodynamic responses caused by endotracheal intubation in elderly hypertensive patients. methods: Sixty elderly patients (≥ 60 years old) with controlled hypertension and classified as American Society of Anesthesiologists physical status II, scheduled to undergo elective noncardiac surgery, were randomly selected and assigned to 2 groups. Group C received normal saline, and group D received 0.5 μg/kg dexmedetomidine intravenously over 10 min just before endotracheal intubation. Systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and heart rate (HR) were recorded preoperatively in the ward, immediately after study drug administration, and at 1, 3, and 5 min after endotracheal intubation. results: Compared to group C, group D showed significantly lower SBP and MAP at 1, 3, and 5 min as well as significantly lower DBP and HR at 3 and 5 min after endotracheal intubations. conclusion: In elderly patients with hypertension, administering a single pre-anesthetic dose of dexmedetomidine (0.5 μg/kg) significantly reduced the hemodynamic responses during endotracheal intubation.